2015
DOI: 10.1177/1082013214568795
|View full text |Cite
|
Sign up to set email alerts
|

Time–intensity profile of pitanga nectar (Eugenia unifloraL.) with different sweeteners: Sweetness and bitterness

Abstract: Pitanga has been used by the Brazilian food industry mainly for juice production. This fruit shows good economic potential due to its high concentration of vitamins and minerals. The aim of the present work was to characterize the time-intensity profile of pitanga nectar sweetened with different sweeteners to verify differences on the perception of sweet and bitter tastes. The sweeteners used to replace sucrose were sucralose, aspartame, stevia 40% rebaudioside A, stevia 95% rebaudioside A, neotame, and 2:1 cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 36 publications
1
12
0
Order By: Relevance
“…Dessimoni-Pinto et al (2011) found that jabuticaba results in a jelly with high phenolic content. Pitanga is a fruit that has stood out in particular, due to its high vitamin C content (Lima et al, 2002;Freitas et al, 2016), being even higher than in orange. According to Bianchini et al (2016) the fruit of the cambuci tree also have been highlighted for being an excellent source of vitamin C. Thus, it can be seen that when jabuticaba is mixed with cambuci or with pitanga the jellies obtained have a higher phenolics content and antioxidant activity than jellies obtained from these two fruits, isolated (Table 6).…”
Section: Nutritional Characteristics Of Mixed Brazilian Native Fruit mentioning
confidence: 99%
See 1 more Smart Citation
“…Dessimoni-Pinto et al (2011) found that jabuticaba results in a jelly with high phenolic content. Pitanga is a fruit that has stood out in particular, due to its high vitamin C content (Lima et al, 2002;Freitas et al, 2016), being even higher than in orange. According to Bianchini et al (2016) the fruit of the cambuci tree also have been highlighted for being an excellent source of vitamin C. Thus, it can be seen that when jabuticaba is mixed with cambuci or with pitanga the jellies obtained have a higher phenolics content and antioxidant activity than jellies obtained from these two fruits, isolated (Table 6).…”
Section: Nutritional Characteristics Of Mixed Brazilian Native Fruit mentioning
confidence: 99%
“…The pitanga (Eugenia uniflora L.) is also a Brazilian Native fruit, common in central Brazilian to northern Argentina (Donadio et al, 2002). Ot is a fruit that has colorations ranging from orange and dark red to purple and has good economic capacity due to its high vitamins, minerals and carotenoids (Lima et al, 2002;Freitas et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Time-intensity analysis has been widely used in different food matrices, such as fruit nectar (Freitas et al, 2015), chocolate (Palazzo and Bolini, 2014), fruit jelly (Souza et al, 2013), and white wine (Sokolowsky and Fischer, 2012), mainly to verify sensory perception of sweet, acid and bitter taste, viscosity, and melting in various products.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, they describe the mean velocity, duration, and intensity perceived for a single stimulus (Amerine et al, 1965). Time-intensity analysis has been used in research on different types of products (Freitas et al, 2015;Bolini, 2009, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, there is a growing awareness about the adverse effects of sugar consumption, which would result in a high glycemic index and accordingly an acute increase in plasma glucose and insulin levels after consumption (Aidoo et al., 2017; Feizollahi et al., 2018). Due to these reasons, the suitable products for these groups should be formulated with sucrose substitutes (Freitas et al., 2016; Kazemalilou and Alizadeh, 2017).…”
Section: Introductionmentioning
confidence: 99%